Analysis of blood donors' characteristics and deferrals related to COVID-19 in Iran. (April 2021) - Rafiee, Mohammad Hessam; Kafiabad, Sedigheh Amini; Maghsudlu, Mahtab
Highlights: This study analyzed the COVID-19 deferrals of blood volunteers during the COVID-19 outbreak in Iran. The blood donations dropped to 26.09 % in Iran at 2020. The blood shortage was due to reduction in the number of voluntary blood donors. Abstract: Background: With the outbreak of the coronavirus disease in 2019, called COVID-19, Iranian Blood Transfusion Organization (IBTO) implemented the new deferrals. This study analyzed the COVID-19 deferrals of blood volunteers and compared the demographics, deferrals, and the donor status during the COVID-19 outbreak in 2019. Study design and methods: Data were collected from the integrated blood donor database between Feb-Apr 2019 and 2020. Deferral reasons of COVID-19 were categorized as: those who have symptoms or live with a symptomatic family member, have direct exposure with a confirmed case, have travelled from the outbreak affected areas, and have fully recovered from confirmed COVID-19. The z-test analysis was used, and 95 % confidence intervals were calculated to compare the sample proportions. Results: The blood donations dropped to 26.09 % in 2020. The percent change of first-time blood donors, female donors, and donors within the age group of 45−54 years old was significantly greater in 2020 than the same time frame in 2019 (p < 0.05). The results showed that 0.58 % of volunteers were deferred from blood donation to avoid transmission of SARS-CoV-2. The rate of COVID-19 deferrals in all types except travelling to affected areas has increased in the second 30-day of the study (p < 0.05). Conclusion: The blood shortage that occurred during the COVID-19 outbreak was not due to increased deferral for COVID-19, but it was mostly due to a decrease in the number of volunteers who referred to BTCs.